Geriatric Emergency Medicine: challenge of the present and future - Madalys Díaz Díaz; Pablo Sebastián Silveira Hernández; Marta Rosa Ferriol Rodríguez (Acta Médica del Centro, 2014)
Population aging has had a significant impact on public health and health care in Cuba. The province of Villa Clara is the highest degree of aging (21.9%); this population subgroup contributes between 25 and 40% of visits to the Emergency Services. The models of care for adults in these services are not adapted to the geriatric patient, they are unknown of their peculiarities and it is belittled the functional, mental and social assessment. A geriatric assessment adapted to the dynamics of the Emergency Services help to establish a plan of specific cares to each elderly patient with acute medical illness requiring these services and preserve the quality and life expectancy that the NHS has achieved.